Kriteria Calon Pemimpin Negara dan Mekanisme Pencalonannya di Negara Republik Indonesia dalam Pandangan Fiqih Siyasah - Tofa Fidyansyah; Siti Ngainnur Rohmah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Leadership has a major influence on the political and state life of a nation. A leader will also determine the progress and retreat of a country. This paper provides an understanding of the criteria for candidate state leaders whose mechanisms have been determined in the laws and regulations of the Republic of Indonesia and the criteria for candidate state leaders in the view of fiqh siyasah. This study uses a qualitative method with a literature approach. The data in this study were obtained from binding legal materials consisting of legislation, court decisions, legal theory, books, scientific writings and legal journals. The results of this study state that the criteria for candidates for state leaders in the Republic of Indonesia as stated in the laws and regulations have several similarities with the criteria for candidate leaders according to Fiqih Siyasah, the presidential election of the Republic of Indonesia in the period before 2009 was carried out with the concept of Bay'at Ahl al-Hall wa al-'Aqd, the presidential election is carried out in the deliberations of the people's representatives who are in the People's Consultative Assembly (MPR), appointed by the assembly, and when the term of office ends, an accountability report will be asked to the assembly that appointed it. The presidential election of the Republic of Indonesia, in the period after 2009 was carried out by way of direct elections through elections, all levels of society who have the right to vote can make their choice directly, no longer through representatives by people's representatives. But the weakness is that the elected president is not asked to report an accountability report at the end of his term of office.Keywords: Criteria for prospective leaders, mechanisms, fiqh siyasah. AbstrakKepemimpinan berpangaruh besar terhadap kehidupan berpolitik dan bernegara suatu bangsa. Seorang pemimpin juga akan menentukan maju mundurnya sebuah negara. Tulisan ini memberikan pemahaman bagaimana kriteria calon pemimpin negara yang sudah ditetapkan mekanismenya dalam peraturan perundang-undangan Republik Indonesia dan kriteria calon pemimpin negara dalam pandangan fikih siyasah. Penelitian ini menggunakan metode kualitatif dengan pendekatan literatur. Data dalam penelitian ini diperoleh dari bahan-bahan hukum yang mengikat yang terdiri dari perundang-undangan, keputusan pengadilan, teori hukum, buku-buku, tulisan-tulisan ilmiah dan jurnal hukum. Hasil penelitian ini menyatakan bahwa kriteria calon pemimpin negara di Republik Indonesia yang tertuang dalam peraturan perundang-undangan memiliki beberapa persamaan dengan kriteria calon pemimpin menurut Fiqih Siyasah, Pemilihan presiden Republik Indonesia dalam kurun waktu sebelum tahun 2009 dilaksanakan dengan konsep Bay’at Ahl al-Hall wa al-‘Aqd, pemilihan presiden dilakukan di dalam musyawarah para wakil rakyat yang berada di dalam Majelis Permusyawaratan Rakyat (MPR), diangkat oleh majelis, dan ketika berakhir masa jabatan akan dimintai laporan pertanggung jawaban kepada majelis yang mengangkatnya. Pemilihan presiden Republik Indonesia, dalam kurun waktu sesudah tahun 2009 dilakukan dengan cara pemilihan langsung melalui pemilu, semua lapisan masyarakat yang mempunyai hak pilih bisa menentukan pilihannya secara langsung, tidak lagi melalui perwakilan oleh wakil rakyat. Tetapi kelemahannya presiden terpilih tidak dimintai laporan pertanggung jawaban di akhir masa jabatan. Kata kunci : Kriteria calon pemimpin, mekanisme, fiqih siyasah.